Comparative study of the production of closed water fishery resources inside and outside the embankment of Meghna Dhonagoda irrigation project (Bangladesh Journal of Zoology, 2012)
A comparative carried out was done on the closed water fishery resources between inside and outside the embankment of Meghna Dhonagoda Irrigation Project (MDIP). This research explores that the culture fishery has been developed inside the MDIP project area after the construction of Flood Control, Drainage and Irrigation (FCDI) Project. The average production of fishes in closed water (ponds and borrow pits) was higher inside (2374.39 kg/ha and 2436.37 kg/ha) than outside (1984.32 kg/ha and 2075.01 kg/ha) in 2003-2004 and 2004- 2005. The significant difference (p